Investigation of some structural and functional parameters of an oak forest from North-East Rhodopa Mountains - Ljubenova, Mariana (Macedonian Journal of Ecology and Environment, 1996)
Nowadays, humanity gets more and more conscious of the fact that condition of the biosphere, as well as further existence of men are determined by the condition of our planet vegetation cover. The study of space and functional structure of the vegetation associations is a basic precondition for increasing the biological productivity, the stability of the biogeocoenoses and their importance for the healing of the ecological environment in separate districts as well as of the Earth as a whole. The objects of this study are some structural (species, composition, plenitude, numbers of the cenopopulations, layer structure of the phytocoenose, layer and functional structure of the phytomass) and functional (overground annual production, dynamics of wood accumulation, net assimilation, intensity of the biological turnover) parameters of a xerothermal association from the North-eastern Rhodopa mountains.